Antihypertensive and bovine plasma oxidation‐inhibitory activities of spent hen meat protein hydrolysates. Issue 4 (17th April 2017) - Udenigwe, Chibuike C.; Girgih, Abraham T.; Mohan, Aishwarya; Gong, Min; Malomo, Sunday A.; Aluko, Rotimi E.
Abstract: Hydrolysis of spent hen meat proteins with pepsin and pepsin + pancreatin yielded SPH‐P and SPH‐PPc hydrolysates, respectively. The hydrolysates dose‐dependently inhibited activities of human recombinant renin (IC50 0.34 and 0.52 mg/mL, respectively) and angiotensin I‐converting enzyme (ACE, IC50 0.64 and 0.42 mg/mL, respectively). The hydrolysates had lower cysteine and tryptophan contents but similar contents of other amino acids when compared with the parent spent hen protein isolate. SPH‐P, but not SPH‐PPc, dose‐dependently increased the sulfhydryl content and ferric reducing antioxidant capacity of bovine plasma oxidized with H2 O2, which demonstrate its protective effect against oxidation. Oral administration of the protein hydrolysates to spontaneously hypertensive rats at 200 mg/kg body weight induced −26.5 mmHg (SPH‐P) and −35.8 mmHg (SPH‐PPc) maximum lowering of systolic blood pressure after 2 hr. The antihypertensive effects of the hydrolysates were reduced at 8 hr and completely lost at 24 hr post‐gavage. Practical applications: Bioactive peptides have been produced from various protein sources and the nature of the matrix can influence their enzymatic release. Our findings demonstrate that spent hen meat proteins can be used as precursors of antioxidative and antihypertensive peptides. In vivo effects observed in hypertensive rats indicate that the peptides, or their derivatives, are bioavailable to exert short‐term blood pressure reduction. Valourization of the poultry by‐products can be pursued in formulating meat peptide‐based functional foods. Such products can be used for managing oxidative stress and hypertension‐related health problems.